From a meso- to micro-scale connectome: array tomography and mGRASP - Rah, Jong-Cheol; Feng, Linqing; Druckmann, Shaul; Lee, Hojin; Kim, Jinhyun (FRONTIERS RESEARCH FOUNDATION, 2015)
Mapping mammalian synaptic connectivity has long been an important goal of neuroscience because knowing how neurons and brain areas are connected underpins an understanding of brain function. Meeting this goal requires advanced techniques with single synapse resolution and large-scale capacity, especially at multiple scales tethering the meso- and micro-scale connectome. Among several advanced LM-based connectome technologies, Array Tomography (AT) and mammalian GFP- Reconstitution Across Synaptic Partners (mGRASP) can provide relatively high-throughput mapping synaptic connectivity at multiple scales. AT- and mGRASP-assisted circuit mapping (ATing and mGRASPing), combined with techniques such as retrograde virus, brain clearing techniques, and activity indicators will help unlock the secrets of complex neural circuits. Here, we discuss these useful new tools to enable mapping of brain circuits at multiple scales, some functional implications of spatial synaptic distribution, and future challenges and directions of these endeavors.
Keywords: VESICULAR GLUTAMATE TRANSPORTER-1; MAMMALIAN SYNAPTIC CONNECTIVITY; NEURONAL CIRCUIT RECONSTRUCTION; VISUAL CORTICAL-NEURONS; PYRAMIDAL NEURONS; IN-VIVO; ELECTRON-MICROSCOPY; NEURAL CIRCUITS; MOUSE-BRAIN; DENDRITIC EXCITABILITY